Respuesta :

Given : One end point = -6 +3i, midpoint = -13 + i.

To find : Missing end point.

Solution: We know mid-point formula,

Mid-Point =[tex]\frac{First End Point+ Second End Point  }{2}[/tex].

Let us take missing mid-point x.

Plugging values of First End Point and Second End Point in the above formula.

We get,

[tex]\frac{-6 +3i+x}{2}[tex] = [tex]-13+i[/tex]

[tex]\frac{-6 +3i+x}{2} * 2 = 2* (-13+i)[/tex]

[tex]-6+3i+x = -26 +2i[/tex]

Adding 6 on both sides.

-6+3i+x+6 = -26 +2i+6

3i+x = -20+2i.

Subtracting both sides by 3i.

3i+x-3i = -20+2i-3i.

x= -20-i

Therefore, missing end point is -20-i.


Answer:

C. switching the endpoint and midpoint in her original equations

Step-by-step explanation:

just took it